Effect of an Emollient Emulsion Containing 15.0% of Caprylic/Capric Triglyceride on the Urocanic Acid of the Stratum Corneum - Alicio Vitorino de Souza Neto; Débora Quintas Balla; Thalita Marcilio Candido; Catarina Rosado; André Rolim Baby; Fabiana Vieira Lima Solino Pessoa (Life, 2023)
Natural moisturizing factor (NMF) includes several compounds in the stratum corneum (SC), among them, urocanic acid (UCA). Ultraviolet (UV) exposure turns the trans-UCA of the SC into its cis isomer. We investigated the impact of a topical emollient emulsion treatment on the UCA isomers of the SC exposed to artificial UV stress. Aliquots of emollient emulsion were applied in healthy subjects for 2 h on delimited areas of the volar forearm, then, the SC was removed by tape stripping. Tapes were irradiated in a solar simulator chamber and a high performance liquid chromatograph was used to quantify UCA isomers from stripped SC extract. The amount of both UCA isomers were almost twice higher in the SC treated with the emollient emulsion. We also observed that the UV irradiation elevated the amount of the cis/trans UCA ratio on the SC (non-treated and treated), suggesting that the emollient sample was not able to avoid the UCA isomerization. The in vivo tests corroborated with the UCA data obtained ex vivo, since we found an increase in the superficial skin hydration with respective reduction of the TEWL, probably occurring by the occlusion performed by the emollient emulsion containing 15.0% w/w of caprylic/capric triglyceride.